Fe-Catalyzed reactions of 2-chloro-1,7-dienes and allylmalonates - Drabina, Pavel; Nečas, David; Sedlák, Miloš; Kotora, Martin (Elsevier, 2007)
Fe(III)(BIAP)Cl-3 complex catalyzes alkylative cyclization of 2-chloro-1,7-heptadiene in the presence of triethylaluminum. It also catalyzes deallylation of certain 2-allyl-2-substituted malonates under the same reaction conditions. (c) 2007 Elsevier Ltd. All rights reserved.